“serious art”: colombian art and the historical european vanguard in 1922 (2008)
The article analizes the reception of European avantgardeart in Colombia through the analysis of the discussionsaroused by the exposition of Modern FrenchPainting, seen in Bogota and Medellin in 1922. RafaelTavera, Roberto Pizano and Gustavo Santos were themain voices in the debate. Their criticisms are studied inorder to shed light on some aspects pertaining the cultural,artistic and institutional contexts that characterizedthe conservative position assumed by national artistsagainst to the European avant-garde at the beginningof the twentieth century.